Functional antagonism between CagA and DLC1 in gastric cancer - Hinsenkamp, Isabel; Köhler, Jan Philipp; Flächsenhaar, Christoph; Hitkova, Ivana; Meessen, Sabine Eberhart; Gaiser, Timo; Wieland, Thomas; Weiß, Christel; Röcken, Christoph; Mowat, Michael; Quante, Michael; Taxauer, Karin; et al. (Cell death discovery, 2022)
Helicobacter (H.) pylori-induced gastritis is a risk factor for gastric cancer (GC). Deleted-in-liver-cancer-1 (DLC1/ARHGAP7) inhibits RHOA, a downstream mediator of virulence factor cytotoxin-A (CagA) signalling and driver of consensus-molecular-subtype-2 diffuse GC. DLC1 located to enterochromaffin-like and MIST1+ stem/chief cells in the stomach. DLC1+ cells were reduced in H. pylori gastritis and GC, and in mice infected with H. pylori. DLC1 positivity inversely correlated with tumour progression in patients. GC cells retained an N-terminal truncation variant DLC1v4 in contrast to full-length DLC1v1 in non-neoplastic tissues. H. pylori and CagA downregulated DLC1v1/4 promoter activities. DLC1v1/4 inhibited cell migration and counteracted CagA-driven stress phenotypes enforcing focal adhesion. CagA and DLC1 interacted via their N- and C-terminal domains, proposing that DLC1 protects against H. pylori by neutralising CagA. H. pylori-induced DLC1 loss is an early molecular event, which makes it a potential marker or target for subtype-aware cancer prevention or therapy.